On Studying the Effectiveness of Extended Finite State Machine Based Test Selection Criteria - Jadoon, Noshad Khan (2015)
A Master of Science thesis in Computer Engineering by Noshad Khan Jadoon entitled, "On Studying the Effectiveness of Extended Finite State Machine Based Test Selection Criteria," submitted in July 2015. Thesis advisor is Dr. Khaled El-Fakih. Soft and hard copy available.